Environmental Fiqh Beyond Moral Authority: Translational Enforceability in Climate Governance - Muhammad Fauzi F Bachrong (Punggawa Legacy Center, 2026)
Climate change has increasingly been governed through carbon measurement, emission targets, and administrative control. This article examines a less explored question, namely how environmental fiqh can acquire policy force within a national legal system that does not formally recognize fatwa as legislation. Focusing on Fatwa MUI No. 86 of 2023 on the law of controlling global climate change, the study uses normative legal research with statutory, conceptual, and maqāṣid-based analysis. The article argues that the fatwa gives climate change a juridical form by linking ecological harm to mafsadah, mitigation to responsibility, and climate restraint to the protection of public welfare. Yet this religious-normative force does not create direct legal enforceability under Indonesian national law. A fatwa cannot impose sanctions, alter licences, or create public duties without being reformulated by competent state institutions. The main contribution lies in the concept of translational enforceability. Environmental fiqh becomes legally meaningful when its principles are selected, translated into public reasons, and embedded into valid policy instruments such as administrative standards, climate education, procurement rules, reporting duties, or licensing requirements. This model avoids both symbolic adoption and direct incorporation. It preserves constitutional legality while allowing Islamic legal reasoning to enrich climate governance through harm prevention, just transition, and intergenerational responsibility.